2012
DOI: 10.1007/s11357-011-9375-5
|View full text |Cite
|
Sign up to set email alerts
|

Reversible epigenetic histone modifications and Bdnf expression in neurons with aging and from a mouse model of Alzheimer’s disease

Abstract: With aging and Alzheimer's disease (AD), there is an increased sensitivity to stress along with declines in the memory-associated neurotrophin brainderived neurotrophic factor in AD. We have replicated this aging phenotype in cultured neurons from aged mice despite being grown in the same environmental conditions as young neurons. This led us to hypothesize that age-related differences in epigenetic acetylation and methylation of histones are associated with age-related gene regulation. We cultured hippocampal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
63
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(72 citation statements)
references
References 73 publications
(84 reference statements)
9
63
0
Order By: Relevance
“…Hypoacetylation of neuroplasticity genes lead to transcriptional downregulation of genes essential for synaptic maintenance, function and neurotransmission. Studies from aging mice and rat brains have shown a reduced acetylation level of H3K9 and H4K12 as well as increased HDAC2 expression, the latter resulting in a hypoacetylated BDNF promoter-region [285][286][287]. In fact, a perturbed HDAC2-BDNF feedback loop has been suggested as a common feature of aging and neurodegeneration.…”
Section: Lysine Acetylation and Cognitive Declinementioning
confidence: 99%
“…Hypoacetylation of neuroplasticity genes lead to transcriptional downregulation of genes essential for synaptic maintenance, function and neurotransmission. Studies from aging mice and rat brains have shown a reduced acetylation level of H3K9 and H4K12 as well as increased HDAC2 expression, the latter resulting in a hypoacetylated BDNF promoter-region [285][286][287]. In fact, a perturbed HDAC2-BDNF feedback loop has been suggested as a common feature of aging and neurodegeneration.…”
Section: Lysine Acetylation and Cognitive Declinementioning
confidence: 99%
“…H3K9 methylation is found to increase with age, and is linked to cognitive decline. Perhaps as a further link with pathological aging, H3K9 methylation was increased in the brains of 3xTg-AD mouse model of Alzheimer's disease [55].…”
Section: Evidence Of H3k9me2 In Neurodegenerationmentioning
confidence: 99%
“…In a study on both aging and AD, global decrease of 5-mC was observed during the aging process, while increase of 5-hmC was observed in 3xTgAD mouse compared to wild-type control (Cadena-del-Castillo et al, 2014). In a study on histone modification, the level of H3/H4 acetylation started to increase at 4 months of age in 3xTgAD mouse, which is a distinctive feature compared to wild-type mice (Walker, LaFerla, Oddo, & Brewer, 2013). In a microRNA study, the upregulation of microRNA in 3xTgAD mouse converged to the regulation of synaptic function, and miR-325 was identified as a key player in both AD pathology development and response to environmental enrichment (Barak et al, 2015).…”
Section: Animal Studies Of Admentioning
confidence: 96%